2016
DOI: 10.19164/ijcle.v23i3.530
|View full text |Cite
|
Sign up to set email alerts
|

To work or not to work... Before law school: apprehension, confidence, and cynicism among law students

Abstract: Most socio-legal scholarship does not examine pre-law school preparation, more specifically, work experience. The recent American economic recession brought many working adults back into the fold of school. With regard to legal education in particular, how might work experience before law school affect students' perceptions of the profession, themselves, and their career trajectories? And, how do these experiences vary between law schools, and among law students?Drawing on an ethnographic study at two divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…It is not uncommon in law school to feel unprepared where many students with attorney family members take on internships to bolster their legal familiarity before starting law school. Pan’s (2016) findings corroborate Sara’s sentiment. Students who worked before commencing law school were generally more confident about their abilities to successfully complete the rigorous professional training when compared with their peers who transitioned immediately to law school.…”
Section: Findings: Experiencing Elite Higher Education As Racially Issupporting
confidence: 54%
See 2 more Smart Citations
“…It is not uncommon in law school to feel unprepared where many students with attorney family members take on internships to bolster their legal familiarity before starting law school. Pan’s (2016) findings corroborate Sara’s sentiment. Students who worked before commencing law school were generally more confident about their abilities to successfully complete the rigorous professional training when compared with their peers who transitioned immediately to law school.…”
Section: Findings: Experiencing Elite Higher Education As Racially Issupporting
confidence: 54%
“…For example, Waters (1999) found that despite West Indian New Yorkers’ assertion as Trinidadian, Guyanese, or Jamaican, their skin color and phenotype resulted in their racialized ascription as black. And scholars of race and ethnicity claim that panethnicity formation occurs through a process of racialization reinforced by external forces in concert with the mobilization of a common identity by insiders (Brown and Jones 2015; Pan 2015; Pan 2017a, 2017b; Reyes 2017, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation